Resident evil [videorecording] - Eichinger, Bernd; Anderson, Paul W.S.; Eichinger, Bernd ([Culver City, CA : Columbia TriStar Home Video, 2002)
Something terrible is lurking in the hive, a vast underground genetic research facility run by the Umbrella Corporation, a faceless bio-engineering conglomerate. Adeadly viral outbreak occurs, and in response, the Red Queen - a vast supercomputer that controls and monitors the hive - seals the entire facility to contain the leak, killing all the trapped employes. Alice and Rain must lead fellow commandos to isolate the virus that has wiped out Umbrella's entire research staff. The team soon discovers, however, that the workers are not really dead. They are now the ravenous undead, and they are prowling the hive. One bite or stratch from an undead causes infection and worse, instant transformation into their kind.
Executive producer, Robert Kulzer ; story, Alan McElroy ; screenplay, Paul W. S. Anderson
Cast: Milla Jovovich (Alice), Michelle Rodriguez (Rain)
VCD format
Keywords: Evil in motion pictures; Death in motion pictures